Obesity in the United States – Dysbiosis from Exposure to Low-Dose Antibiotics? - Riley, Lee W.; Raphael, Eva; Faerstein, Eduardo (Frontiers in Public Health, 2013)
The rapid increase in obesity prevalence in the United States in the last 20 years is unprecedented and not well explained. Here, we explore a hypothesis that the obesity epidemic may be driven by population-wide chronic exposures to low-residue antibiotics that have increasingly entered the American food chain over the same time period. We propose this hypothesis based on two recent bodies of published reports—1) those that provide evidence for the spread of antibiotics into the American food chain, and 2) those that examine the relationship between the gut microbiota and body physiology. The livestock use of antimicrobial agents has sharply increased in the US over the same 20-year period of the obesity epidemic, especially with the expansion of intensified livestock production, such as the concentrated animal feeding operations (CAFOs). Observational and experimental studies support the idea that changes in the intestinal microbiota exert a profound effect on body physiology. We propose that chronic exposures to low-residue antimicrobial drugs in food could disrupt the equilibrium state of intestinal microbiota and cause dysbiosis that can contribute to changes in body physiology. The obesity epidemic in the United States may be partly driven by the mass exposure of Americans to food containing low-residue antimicrobial agents. While this hypothesis cannot discount the impact of diet and other factors associated with obesity, we believe studies are warranted to consider this possible driver of the epidemic.